Interpretasi Data Seismik Refraksi Menggunakan Metode Reciprocal Hawkins dan Sofware SRIM (Studi Kasus Daerah Sioux Park, Rapid City, South Dakota, USA) - Wahyuningrum, Sri; Yulianto, Gatot; Nurwidyanto, M. Irham (BERKALA FISIKA, 2006)
Data processing of seismic refraction has been done. This data processing was the secondary data from seismic measurement result in the Sioux Park area, Rapid City, South Dakota, USA using EG refraction & G Geometrics Model ES-1210 seismic refraction instrument made in America with 12 geophones. The seismic refraction data processing was to determined the velocity and the deepness of eachs layer, and make geology under surface model then to interpreted the the data processing result using Reciprocal Hawkins method and SRIM software. On the seismic data processing used Reciprocal Hawkins method and SRIM (Seismic Refraction Inverse Modelling) software. Reciprocal Hawkins method used time depth concept and SRIM software used delay time concept. The time depth value or the delay time value was same with a half value of intercept time.The result from the data processing using Reciprocal Hawkins method was obtained threes layer, that are the seismic wave velocity of the first layer is 1013 ft/s, the second layer is 4007 ft/s and the third layer is 6887 ft/s. While the result of the deepness calculation obtained the deep of first layer range is 0,93 ft – 11,24 ft, the second layer ranging is 8,72 ft – 19,38 ft and from data processing the result using SRIM software obtained seismic wave velocity of the first layer is 970 ft/s, the second layer is 3485 ft/s and the third layer is 6150 ft/s, while the result of deepness calculation of the first layer range is 0,10 ft – 7,20 ft, the second layer range from 3,40 ft – 27,00 ft. From the under surface image model can be interpreted that the first layer is mouldy  layer which represent cover layer, the second layer is clay stone layer, sand ( dry, having the pass character) and third layer is napal stone at Spearfish formation which has impermeable characteristic or waterproof. Key words: delay time, intercept time, Reciprocal Hawkins method, seismic refraction